Heliodor – Rubinkowski – Twardowski. Trzy „romanse” wobec ciała i seksualności - Słomak, Iwona (Śląskie Studia Polonistyczne, 2011)
The author suspiciously analyses the work by Paweł Bohuszewicz on the Polish Baroque romance. She brings the narratological method closer, yet presents a series of doubts and objections against the means of using „fashionable” contemporary humanist works in the work in question. References to Baudrillard’s conception seem unconvincing. Equally unsuccessful was the usage of Foucault’s knowledge about body in Baroque works since their main qualities are more accurately defined by the context of Ignatian or Teresian corporality. One should also question the genological findings achieved by Bohuszewicz, whose conception of literary genres is a combination of old arrangements with too modern ideas, as a result of which still binding conceptions by Opacki and others were not taken into consideration.